Projeto de melhoria para reduzir o tempo de espera por cirurgia urológica eletiva em um hospital geral - Valim, Roger Pereira (2022)
Introduction: The long waiting times issue in healthcare is a priority for developed and developing countries. The guarantee of timely access to health permeates clinical, psychological, social, ethical, economic and legal aspects. Despite the relevance of the topic, studies aimed at the development of methods to reduce waiting lists in Brazil are limited. Objective: Reduce the waiting time for elective urological surgeries, through an improvement project, based on quality management and with an emphasis on flows and processes' redesign. Methodology: The quality improvement project was carried out at Hospital Geral Dr. Waldemar Alcântara, with a quasi-experimental design, without a parallel control group. After a qualitative analysis of the problem, an intervention in the work processes was planned and carried out in order to improve the integration between medical appointments and diagnostic exams, optimize the activities of professionals, establish goals in the process and implement a system to monitor the journey of care of patients. The effects of actions were measured for seven consecutive months through the average total waiting time. The time of surgery indication, the time of scheduling the procedure and the number of surgeries performed were also measured. Results: After the intervention, there was an absolute improvement of 70 days in the average total waiting time (100 days versus 30 days), corresponding to a 70% reduction in waiting. The mean time for surgery was reduced by 76% (70 days versus 17 days). Average scheduling time decreased from 30 to 13 days, 55% improvement. In the trend graph, it is possible to observe that, after the intervention, the results remained below the median of the previous period, throughout the evaluation period (seven consecutive months), configuring a pattern change with a value of p<0.05. Before the intervention, only 6.5% of the patients were operated on within 20 days. After the intervention, that number rose to 60%. The number of elective surgeries also increased by 77% from one period to the next. Conclusions: The interventions performed were able to promote more timely access for patients to elective surgical procedures, improving the quality of health care.